Effect of different phosphoms sources and soil amendments on the yield and quality of aswagandh (Withania somnifera Dunal) under acid soils - Sumaiyah Sumaiyah, D Muthumanickam, Murugesan Murugesan (Journal of Spices and Aromatic Crops, 2002)
Trials were conducted in acid soil at Yercaud (Tamil Nadu, India) with the objective of identifying the ideal source of phosphorus and soil amendment in aswagandh (Withania somnifera Dunal) in acid soils. Application of 60 kg ha-1 P205 as rock phosphate along with dolamite (5.688 t ha-1) for increasing the yield resulted in the highest dry root yield of 814.5 kg ha-1 in the present study. There was also an improvement in the total withanolides content due to the application of dolomite and rock phosphate.